The Effect of Mixing Time and Rotation Speed on the Consistency of Dough Viscosity in a Horizontal Mixer - Rizza, Muhammad Akhlis; Dharsono, Ekky Yovianto; Murdani, Anggit; Monasari, Ratna; Amrullah, Radhi Nurvian; Aji, Supa Kusuma; Khaerudin, Dian Noorvy (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Cassava must go through several manufacturing processes before it becomes chips on the market, including the process of stirring the dough. The stirring process is an important stage in various food industries. In the stirring process, the viscosity change in the dough is influenced by various factors, including the stirring process time and speed in stirring. Research on dough viscosity is important because it is directly related to the quality of the final product. The purpose of this study is to provide recommendations to users, both in the context of using horizontal mixers and the process of making similar products. The type of research used is quantitative research based on experimental methods that aim to test a hypothesis by collecting data that can be measured using statistics, mathematics, and computing. The independent variables in this study are rotation speed (20, 40, and 80 rpm) and stirring time (5 minutes, 10 minutes, and 15 minutes). From these independent variables calculations and data analysis, the optimal setting was obtained using a rotation speed of 80 rpm and a stirring time of 15 minutes with a dough viscosity of 1411.12 PaS. The rotation speed of 80 rpm has more even data or more consistent data compared to the rotation speed values of 20 rpm and 40 rpm.